Mass spectrometry for the analysis of pesticide residues and their metabolites - Tsipi, Despina, 1955-; Botitsi, Helen, 1967-; Economou, Anastassios (Hoboken, New Jersey : John Wiley & Sons, Inc., 2015)
Provides an overview of the use of mass spectrometry (MS) for the analysis of pesticide residues and their metabolites. -Presents state of the-art MS techniques for the identification of pesticides and their transformation products in food and environment -Covers important advances in MS techniques including MS instrumentation and chromatographic separations (e.g. UPLC, HILIC, comprehensive GCxGC) and applications -Illustrates the main sample preparation techniques (SPE, QuEChERS, microextraction) used in combination with MS for the analysis of pesticides -Describes various established and new ionization techniques as well as the main MS platforms, software tools and mass spectral libraries.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Pesticides -- Analysis; Mass spectrometry; Mass spectrometry; Pesticides -- Analysis; TECHNOLOGY & ENGINEERING / Agriculture / General; Electronic books; Electronic books; Electronic books